Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2174/1389450115666141122211549
|View full text |Cite
|
Sign up to set email alerts
|

Insights into a Critical Role of the FOXO3a-FOXM1 Axis in DNA Damage Response and Genotoxic Drug Resistance

Abstract: FOXO3a and FOXM1 are two forkhead transcription factors with antagonistic roles in cancer and DNA damage response. FOXO3a functions like a typical tumour suppressor, whereas FOXM1 is a potent oncogene aberrantly overexpressed in genotoxic resistant cancers. FOXO3a not only represses FOXM1 expression but also its transcriptional output. Recent research has provided novel insights into a central role for FOXO3a and FOXM1 in DNA damage response. The FOXO3a-FOXM1 axis plays a pivotal role in DNA damage repair and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 157 publications
(195 reference statements)
1
72
0
1
Order By: Relevance
“…It is well-established that Akt (PKB)-mediated phosphorylation and inactivation of FOXO3a culminate in cytoplasmic localization and cell proliferation (2,3). Herein, we showed that in the sensitive B-ALL cell lines, RS4,11 and SUP-B15, FOXO3a became dephosphorylated on Akt-targeted sites, Ser253, Thr315, and Thr32 upon dexamethasone treatment, but its phosphorylation was unaffected by dexamethasone in the resistant REH cells.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is well-established that Akt (PKB)-mediated phosphorylation and inactivation of FOXO3a culminate in cytoplasmic localization and cell proliferation (2,3). Herein, we showed that in the sensitive B-ALL cell lines, RS4,11 and SUP-B15, FOXO3a became dephosphorylated on Akt-targeted sites, Ser253, Thr315, and Thr32 upon dexamethasone treatment, but its phosphorylation was unaffected by dexamethasone in the resistant REH cells.…”
Section: Discussionmentioning
confidence: 76%
“…FOXO3a plays an important role in proliferation, apoptosis, autophagy, metabolism, inflammation, differentiation, and stress resistance (3,4). The stability, subcellular localization, the DNA-binding affinity, and the transcriptional activity of FOXO3a are primarily regulated by a complex array of posttranslational modifications (5).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two Forkhead transcription factors forkhead box O3 (FOXO3a) and FOXM1 have been described for their explicit contribution in the DNA damage response. Therefore, ways to explore inhibitors against these two transcription factors are being attempted to augment senescence and cell death in carcinoma 58. Cell cycle checkpoints are potential cellular targets in several carcinomas including the DNA damage response and survival strategies in breast cancer.…”
Section: Small Molecule Inhibition and Non-homologous End Joiningmentioning
confidence: 99%
“…Meanwhile, FOXO3a , aside from affecting PTX actions, regulates the DNA damage response and stimulates the DNA repair pathway, which regulates the sensitivity to drugs that target the DNA repair system such as 5-FU and CIS, among others [15, 16]. Forkhead box M1 ( FOXM1 ) and FOXO3a have been observed to compete in binding to similar DNA sequences, which often results in antagonized transcriptional output that has recently been related to genotoxic drug resistance and the response of various cancers to chemotherapy [17, 18]. …”
Section: Introductionmentioning
confidence: 99%